2023
DOI: 10.1101/2023.04.24.538083
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

RavA-ViaA linksVibrio choleraeCpx- and Zra2- envelope stress to antibiotic response

Abstract: RavA-ViaA were reported to play a role in aminoglycoside sensitivity but the mechanisms remain elusive. Here, we performed competition and survival experiments to confirm that deletion of ravA-viaA increases tolerance of the Gram-negative pathogen Vibrio cholerae to low and high aminoglycoside concentrations, during aerobic growth. Using high throughput strategies in this species, we identify Cpx and Zra2 two-component systems as new partners of RavA-ViaA. We show that the aminoglycoside tolerance of delta rav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…This is partly due to the lack of a clearly observed phenotype upon the deletion of the respective genes. However, various experiments conducted by our group and others have suggested a possible role of this chaperone system in modulating E. coli ’s as well as other Gram-negative bacteria’s sensitivity toward antibiotics ( 7 , 13 , 24 , 25 ). In this regard, studies on the metabolic drivers of persistence in E. coli have implicated fumarate and Frd in increased persistence against antibiotics ( 18 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is partly due to the lack of a clearly observed phenotype upon the deletion of the respective genes. However, various experiments conducted by our group and others have suggested a possible role of this chaperone system in modulating E. coli ’s as well as other Gram-negative bacteria’s sensitivity toward antibiotics ( 7 , 13 , 24 , 25 ). In this regard, studies on the metabolic drivers of persistence in E. coli have implicated fumarate and Frd in increased persistence against antibiotics ( 18 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it was recently suggested that RavA-ViaA facilitate the uptake of aminoglycosides antibiotics across the inner membrane of E. coli under low-energy cellular states ( 24 ). In Vibrio cholerae , the deletion of ravAviaA was found to increase tolerance of the bacteria to aminoglycosides under aerobic conditions but this phenotype requires the presence of an envelope stress two-component system ( 25 ).…”
mentioning
confidence: 99%